Automata, Languages and Programming 36th Internatilonal Collogquium, ICALP 2009, Rhodes, greece, July 5-12, 2009, Proceedings, Part II - Albers, Susanne.; Marchetti-Spaccamela, Alberto.; Matias, Yossi.; Nikoletseas, Sotiris.; Thomas, Wolfgang. (Lecture Notes in Computer Science, 2009)
The two-volume set LNCS 5555 and LNCS 5556 constitutes the refereed proceedings of the 36th International Colloquium on Automata, Languages and Programming, ICALP 2009, held in Rhodes, Greece, in July 2009. The 126 revised full papers (62 papers for track A, 24 for track B, and 22 for track C) presented were carefully reviewed and selected from a total of 370 submissions. The papers are grouped in three major tracks on algorithms, automata, complexity and games; on logic, semantics, theory of programming, as well as on foundations of networked computation: models, algorithms and information management. LNCS 5556 contains 46 contributions of tracks B and C selected from 147 submissions as well as 2 invited lectures. This two-volume set lauches the new subline of Lecture Notes in Computer Science, entitled LNCS Advanced Research in Computing and Software Science (ARCoSS).